Aligning emissions trading and feed-in tariffs in China. (18th May 2016) - Lin, Wenbin; Gu, Alun; Wang, Xin; Liu, Bin
Abstract : In 2013, China launched its domestic pilot emissions trading scheme (ETS) as a cost-effective strategy to reduce CO2 emissions. Theoretically, the ETS can interact with the feed-in tariffs (FITs) applied to renewable energies (REN). This article presents a simple method to demonstrate how FITs can be adjusted based on the evolution of ETS carbon prices in order to provide a cost-effective climate policy package in China. First, by using provincial data and wind and solar power as examples, it calculates the implicit carbon prices that FITs generate in different Chinese provinces and finds that they are much higher than current carbon prices in the pilot ETS. This shows the necessity of using both instruments to guarantee current level incentives to develop REN for climate change purposes, at least in the short and medium terms. Second, by keeping the annual total carbon price level stable (the sum of the implicit FIT carbon price and the ETS carbon price), and taking into account the cost evolution of REN development, this article demonstrates, for the 2018–2020 period, that FIT should decrease at an annual rate of 3.04–4.63% (for wind) and 7.84–8.87% (for solar) based on different growth rates for progressive national ETS carbon prices. Policy relevance There are a number of studies and debates on the interactions between climate policies in Europe in particular, ETS and subsidies for REN. The key issue is that a climate policy package should be cost-efficient and the implementation of one policy should not jeopardise the performance of another. For a country like China, a considerable scale effect on climate target achievement and total cost savings could be produced by the careful design of the climate policy package. FIT and ETS, which are cost-efficient policies if implemented separately, will very probably constitute a major climate policy package in the future in China, which is aiming to limit the use of command-and-control policies. So far, there is some debate on how to reduce FIT for wind power in China due to development cost changes. But discussions are lacking on the linkage between FIT and ETS. This paper fills this gap.